2015
DOI: 10.1111/apm.12408
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Toll‐like receptors in nasal epithelium in allergic rhinitis

Abstract: Toll‐like receptors (TLRs) are important in barrier homeostasis, but their role in airborne allergies is not fully understood. The aim was to evaluate baseline and allergen‐induced expression of TLR proteins in nasal epithelium during allergic rhinitis. Nineteen otherwise healthy non‐smoking volunteers both allergic to birch pollen and non‐allergic controls were enrolled. We took nasal biopsies before and after off‐seasonal intranasal birch pollen or diluent challenge. The expression of epithelial TLR1‐7, TLR9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 48 publications
(74 reference statements)
1
20
1
Order By: Relevance
“…HMGB1 triggers downstream signalling via activating a wide range of receptors, among which TLR4 signalling is thought to be the key for its cytokine‐inducing activities . Binding of additional adaptor proteins with TLR is essential for triggering intracellular signalling cascades, while the myeloid differentiation factor 88 (MyD88) is one of the identified adaptor proteins identified . A previous study has also reported that the acetylation on HMGB1 is highly relevant with the deacetylase activity of SIRT1, indicating that SIRT1 interacts with HMGB1 via deacetylation, thus preventing the release of HMGB1 .…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 triggers downstream signalling via activating a wide range of receptors, among which TLR4 signalling is thought to be the key for its cytokine‐inducing activities . Binding of additional adaptor proteins with TLR is essential for triggering intracellular signalling cascades, while the myeloid differentiation factor 88 (MyD88) is one of the identified adaptor proteins identified . A previous study has also reported that the acetylation on HMGB1 is highly relevant with the deacetylase activity of SIRT1, indicating that SIRT1 interacts with HMGB1 via deacetylation, thus preventing the release of HMGB1 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the inflammatory microenvironment, various cells of the innate immune system (e.g., macrophages and neutrophils) express pattern recognition receptors for the identification of pathogens or pathogen‐associated molecular patterns. During the course of an infection, Toll‐like receptors (a major family of pattern recognition receptors) are essential in the induction and activation of innate immunity in the inflammatory mucosa of the nasal cavity and middle ear . Innate immunity has been hypothesized to serve as an inflammatory inducer and to be involved in immunopathological feedback regulation between AR and cholesteatoma through the release of systemic inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Luukkainen et al (2018) stimulated a co-culture of peripheral blood mononuclear cells and nasal epithelium, differentiated from stem/progenitor cells, with H3N2-virus and detected rapid activation of monocytes, natural killer (NK)-cells and innate T-cells (MAIT and γδ T cells). We demonstrated high baseline nasal epithelial expression of Toll Like receptor (TLR) proteins (TLR1-7, TLR9-10) and MyD88 both in AR and in controls (Renkonen et al, 2015). After off-seasonal intranasal birch pollen challenge, a negative change in the expression score of TLR1 and TLR6 proteins was detected in the atopic group.…”
Section: Upper Airway Epithelial Functions During Ar and Crsmentioning
confidence: 92%